Danish translation, cultural adaptation and initial validation of the Self-Assessment of modes questionnaire (D-SAMQ). (19th May 2021) - Sampedro Pilegaard, Marc; Sithamparanathan, Thivya; Nielsen, Kristina Tomra; Taylor, Renee; Waehrens, Eva Ejlersen
Abstract: Background: The Self-Assessment of Modes Questionnaire (SAMQ) was developed for occupational therapists (OTs) to identify their therapeutic style when interacting with clients. To provide Danish Occupational Therapists (OTs) with access to the SAMQ, a rigorous translation, cultural adaptation and validation are required. Aim: To describe the process of translating and culturally adapting the SAMQ into Danish (D-SAMQ) and examining initial validation of the SAMQ in terms of relevance and comprehensiveness in a Danish context. Material and methods: A 10-step process for translation and cultural adaptation was followed: (1) Preparation, (2) Forward translation, (3) Reconciliation, (4) Back translation, (5) Back-translation review, (6) Harmonization, (7) Cognitive debriefing, (8) Review of cognitive debriefing results and finalization, (9) Proofreading and (10) Final report. The cognitive debriefing also involved validation. Results: Seven OTs and one OT student were included in the cognitive debriefing. Adaptations were made in eight of twenty cases, and modifications regarding the choice of words, sentence structure, and rephrasing were performed. The participants suggested more contextual details in the case descriptions. Conclusion: The SAMQ was translated into Danish (D-SAMQ) and adapted and validated by Danish OTs. The D-SAMQ may enable OTs to identify their therapeutic style, and thereby improve the client–therapist relationship.